Determinant Factors of Liquidity Risk Premium on Indonesian Government Bonds - Hartini, Eka Rathmanty Merry; Hanggraeni, Dewi (The Indonesian Capital Market Review, 2021)
This paper aims to find the determinant factors of the liquidity risk premium on the Indonesian government bonds. There are two liquidity risk premium proxies to be used, the difference of the yield to maturity and the theoretical-yield of the bonds, and the average bid-ask spread of the bonds. The research used the Random Effect panel-data to define the determinant factors of the liquidity risk premium. The result shows that the liquidity-risk premium of Indonesian government bonds is affected by the bond’s characteristics and the financial market condition. The determinant factors are the bond’s age, coupon rate, remaining life, issued amount, type (Sukuk or conventional), and market volatility. We expect this research will enrich the understanding of the liquidity risk on Indonesian government bonds; so that the authorities and the investors could use this in making their decisions.